Taller Alpha Google para mejorar la comprensión lectora en estudiantes de educación secundaria de la Institución Educativa Víctor Andrés Belaunde - Flores Roldán, Adriana Lizet (2018)
The present research work entitled “The workshop Alpha Google to improve reading comprehension in students of secondary education from the educational institution Victor Andrés Belaunde”, aimed to improve the understanding reading of the fifth grade students of secondary school in the area of communication._x000D_ _x000D_ This research is experimental, with quantitative approach and a quasi-experimental design; the population was composed of three sections of fifth grade of secondary school Victor Andrés Belaunde de Trujillo, with a total of 75 female students; also, the sample was determined using nonprobability sampling being made up of 50 students, who applied the test of reading comprehension, individually and face to face; the results then moved to overview pictures side then, using the SPSS statistical 20.00 package, process the results and to represent them in tables and graphs with respective their analysis and interpretation._x000D_ _x000D_ The results obtained showed that the Alpha Google workshop improved reading comprehension of the fifth grade students of secondary school in the area of communication of the I.E. Victor Andrés Belaunde de Trujillo; Since in the post test, the Tc = - 3.231 is greater that the Tt = 1.684, which accepted the alternate hypothesis; i.e., the level of reading comprehension in the experimental group, after the program, control is above the group, therefore it is concluded that the workshop Alpha Google improved the reading comprehension of students from fifth grade high school in the area of communication of the I.E. Victor Andrés Belaunde de Trujillo.